Strategi Pengembangan Usaha Ningsih Florist Di Kelurahan Kakaskasen Dua Kota Tomohon - Purba, Meri Kristina; Pangemanan, Lyndon Reindhart Jacob; Wariki, Barce A. F. (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
This research aims to analyze the business development strategy of Ningsih Florist, which took place during religious and government activities, namely Deville Hardiknas 2024 in Kakaskasen Dua Village, Tomohon City. The research will take place from April to June 2024. The data collection method is by interview method and using a questionnaire. The data collected in this research is primary data obtained from direct interviews with respondents using a list of questions and secondary data in the form of other information related to this research through literature studies. The results of the research show that the strategy for developing the Ningsih Florist business in Kakaskasen Dua Subdistrict, Tomohon City, using SWOT analysis, obtained a matrix at coordinate points (1.88, 1.46), which means that the position is in quadrant 1, namely supporting the growth strategy.